Solve for r
r=\sqrt{37}\approx 6.08276253
r=-\sqrt{37}\approx -6.08276253
r=-6
r=6
Share
Copied to clipboard
\sqrt{r^{2}-36}=r^{2}-36
Subtract 36 from both sides of the equation.
\left(\sqrt{r^{2}-36}\right)^{2}=\left(r^{2}-36\right)^{2}
Square both sides of the equation.
r^{2}-36=\left(r^{2}-36\right)^{2}
Calculate \sqrt{r^{2}-36} to the power of 2 and get r^{2}-36.
r^{2}-36=\left(r^{2}\right)^{2}-72r^{2}+1296
Use binomial theorem \left(a-b\right)^{2}=a^{2}-2ab+b^{2} to expand \left(r^{2}-36\right)^{2}.
r^{2}-36=r^{4}-72r^{2}+1296
To raise a power to another power, multiply the exponents. Multiply 2 and 2 to get 4.
r^{2}-36-r^{4}=-72r^{2}+1296
Subtract r^{4} from both sides.
r^{2}-36-r^{4}+72r^{2}=1296
Add 72r^{2} to both sides.
73r^{2}-36-r^{4}=1296
Combine r^{2} and 72r^{2} to get 73r^{2}.
73r^{2}-36-r^{4}-1296=0
Subtract 1296 from both sides.
73r^{2}-1332-r^{4}=0
Subtract 1296 from -36 to get -1332.
-t^{2}+73t-1332=0
Substitute t for r^{2}.
t=\frac{-73±\sqrt{73^{2}-4\left(-1\right)\left(-1332\right)}}{-2}
All equations of the form ax^{2}+bx+c=0 can be solved using the quadratic formula: \frac{-b±\sqrt{b^{2}-4ac}}{2a}. Substitute -1 for a, 73 for b, and -1332 for c in the quadratic formula.
t=\frac{-73±1}{-2}
Do the calculations.
t=36 t=37
Solve the equation t=\frac{-73±1}{-2} when ± is plus and when ± is minus.
r=6 r=-6 r=\sqrt{37} r=-\sqrt{37}
Since r=t^{2}, the solutions are obtained by evaluating r=±\sqrt{t} for each t.
36+\sqrt{6^{2}-36}=6^{2}
Substitute 6 for r in the equation 36+\sqrt{r^{2}-36}=r^{2}.
36=36
Simplify. The value r=6 satisfies the equation.
36+\sqrt{\left(-6\right)^{2}-36}=\left(-6\right)^{2}
Substitute -6 for r in the equation 36+\sqrt{r^{2}-36}=r^{2}.
36=36
Simplify. The value r=-6 satisfies the equation.
36+\sqrt{\left(\sqrt{37}\right)^{2}-36}=\left(\sqrt{37}\right)^{2}
Substitute \sqrt{37} for r in the equation 36+\sqrt{r^{2}-36}=r^{2}.
37=37
Simplify. The value r=\sqrt{37} satisfies the equation.
36+\sqrt{\left(-\sqrt{37}\right)^{2}-36}=\left(-\sqrt{37}\right)^{2}
Substitute -\sqrt{37} for r in the equation 36+\sqrt{r^{2}-36}=r^{2}.
37=37
Simplify. The value r=-\sqrt{37} satisfies the equation.
r=6 r=-6 r=\sqrt{37} r=-\sqrt{37}
List all solutions of \sqrt{r^{2}-36}=r^{2}-36.
Examples
Quadratic equation
{ x } ^ { 2 } - 4 x - 5 = 0
Trigonometry
4 \sin \theta \cos \theta = 2 \sin \theta
Linear equation
y = 3x + 4
Arithmetic
699 * 533
Matrix
\left[ \begin{array} { l l } { 2 } & { 3 } \\ { 5 } & { 4 } \end{array} \right] \left[ \begin{array} { l l l } { 2 } & { 0 } & { 3 } \\ { -1 } & { 1 } & { 5 } \end{array} \right]
Simultaneous equation
\left. \begin{cases} { 8x+2y = 46 } \\ { 7x+3y = 47 } \end{cases} \right.
Differentiation
\frac { d } { d x } \frac { ( 3 x ^ { 2 } - 2 ) } { ( x - 5 ) }
Integration
\int _ { 0 } ^ { 1 } x e ^ { - x ^ { 2 } } d x
Limits
\lim _{x \rightarrow-3} \frac{x^{2}-9}{x^{2}+2 x-3}